Nanoencapsulation-Based Edible Coating of Essential Oils as a Novel Green Strategy Against Fungal Spoilage, Mycotoxin Contamination, and Quality Deterioration of Stored Fruits: An Overview - Das, Somenath; Ghosh, Abhinanda; Mukherjee, Arpan (Frontiers in Microbiology, 2021)
Currently, applications of essential oils for protection of postharvest fruits against fungal infestation and mycotoxin contamination are being of immense interest and research hotspot in view of their natural origin and possible alternative to hazardous synthetic preservatives. However, the practical applications of essential oils in broad scale industrial sectors have some limitations due to its volatility, less solubility, hydrophobic nature and easy oxidation in environmental conditions. Implementation of nanotechnology for efficient incorporation of essential oils into polymeric matrices develops an emerging and novel strategy to extend its applicability by controlled release and overcome the major limitations. Moreover, different nano-engineered structures (nanoemulsion, suspension, colloidal dispersion and nanoparticles) developed by applying a variety of nanoencapsulation process improve the essential oil efficacy and targeted delivery maintaining the characteristics of food ingredients. Nanoemulsion based edible coating of essential oils into fruits pose an innovative green alternative against fungal infestation and mycotoxin contamination. Encapsulation based coating of essential oils also improve the antifungal, antimycotoxigenic and antioxidant properties, a prerequisite for long term enhancement in fruit shelf life. Furthermore, emulsion based coating of essential oil is also efficient in protection of physico-chemical characteristics viz. farmness, titrable acidity, pH, weight loss, respiration rate and total phenolic contents along with maintenance of organoleptic attributes and nutritional quality. Based on this scenario, the present article deals with advancement in nanoencapsulation based edible coating of essential oil with efficient utilization as novel green safe preservative and develop a green insight in sustainable protection of fruits against fungal and mycotoxin mediated quality deterioration.